Design of Android-Based Reading and Arithmetic Learning Application for Children Aged 4-6 Years - Muzdalifah, Muzdalifah; Hidayat, Indar Kusmanto; Hidayat, Hidayat (Jurnal Ilmiah Multidisiplin Amsir, 2024)
The purpose of this study is to find out how to design and implement an Android-based Learning to Read and Count application for children aged 4 to 6 years, this application is made to facilitate interesting reading and counting amidst the addiction to using mobile phones for children aged 4 to 6 years. This application or system is made using the Java and MySQL programming languages, where this application is used to facilitate learning that is full of modern education by following current technological developments. And based on the results of the implementation, it has succeeded in helping parents in facilitating the use of Android properly.